Triple Cherenkov probe measurements on FTU: calibration and runaway energy spectra. (4th October 2018) - Bagnato, F; Romano, A; Buratti, P; Doria, A; Gabellieri, L; Giovenale, E; Grosso, A; Jakubowski, L; Pacella, D; Piergotti, V; Rabinski, M; Rocchi, G; et al.
Abstract: Characterization and calibration measurements of two Cherenkov probes have been performed in ENEA Frascati's laboratories. Different kinds of radiation have been used, from visible light to x-rays, in order to evaluate possible spurious responses of the probes. Moreover, a preliminary calibration is presented, as well as a first evaluation of the minimum single probe's detectable flux performed through an electron beam of 2.3 MeV. Additional results have been obtained thanks to spectrometry analysis, which gave deeper insights of the phenomena occurring inside the probes. In particular, a continuous emission spectrum, associated to cathodoluminescence, has been observed to dominate in the Cherenkov range, showing that scintillating phenomena are not negligible in this kind of probes. Results on non-thermal electron losses from recent FTU experimental campaigns are also presented. The signals acquired are compared to those from other diagnostics like x-rays, neutron and gamma detectors or plasma magnetic activity, showing good correlation between them. The analysis focuses on the capability and sensitivity of the probes to measure runaway electrons losses with energy discrimination in presence of perturbations due to kinetic and magnetic reconnection phenomena.